Going the whole orang: Darwin, Wallace and the natural history of orangutans. (June 2015) - van Wyhe, John; Kjærgaard, Peter C.
Abstract: This article surveys the European discovery and early ideas about orangutans followed by the contrasting experiences with these animals of the co-founders of evolution by natural selection, Charles Darwin and Alfred Russel Wallace. The first non-human great ape that both of them interacted with was the orangutan. They were both profoundly influenced by what they saw, but the contexts of their observations could hardly be more different. Darwin met orangutans in the Zoological Gardens in London while Wallace saw them in the wild in Borneo. In different ways these observations helped shape their views of human evolution and humanity's place in nature. Their findings played a major role in shaping some of the key questions that were pursued in human evolutionary studies during the rest of the nineteenth century.